2009
DOI: 10.1158/1535-7163.mct-08-1167
|View full text |Cite
|
Sign up to set email alerts
|

Phase I safety, pharmacokinetic, and pharmacogenomic trial of ES-285, a novel marine cytotoxic agent, administered to adult patients with advanced solid tumors

Abstract: A dose-escalation, phase I study evaluated the safety, pharmacokinetics, pharmacogenomics, and efficacy of ES-285, a novel agent isolated from a marine mollusc, in adult cancer patients. Patients received a 24-hour i.v. infusion of ES-285 once every 3 weeks until disease progression or unacceptable toxicity. The starting dose was 4 mg/m 2 . Dose escalation in cohorts of at least three patients proceeded according to the worst toxicity observed in the previous cohort. Twenty-eight patients were treated with 72 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 20 publications
4
40
0
Order By: Relevance
“…Of note, three patients had grade 3 AST increases, and 2 patients had grade 3 ALT increases, one of these adverse drug reactions qualifying as the only DLT observed in this trial. These safety findings are consistent with preclinical investigations and other early clinical studies [6][7][8][9], with reversible transaminase increases reported at the highest doses in concurrent phase I clinical trials with Spisulosine using 3 and 24-h i.v. infusions every 3 weeks.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Of note, three patients had grade 3 AST increases, and 2 patients had grade 3 ALT increases, one of these adverse drug reactions qualifying as the only DLT observed in this trial. These safety findings are consistent with preclinical investigations and other early clinical studies [6][7][8][9], with reversible transaminase increases reported at the highest doses in concurrent phase I clinical trials with Spisulosine using 3 and 24-h i.v. infusions every 3 weeks.…”
Section: Discussionsupporting
confidence: 90%
“…One patient treated with Spisulosine 200 mg/m 2 as a 24-h i.v. infusion developed grade 3 drugrelated central neurotoxicity, which led to the patient's death 6 days after the first administration of the experimental agent [6]. The neurotoxic potential of the drug was confirmed in our study.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations